GEOPOLYMER COMPOSITE MADE THROUGH PARTIAL REPLACING FLY ASH AND SLAG WITH CHEAPER AND LESS USED WASTE PRECURSORS (Nonconventional Technologies Review, 2025)
The research presented in this paper was focused on making a geopolymer composite characterized by the large replacement of the most commonly used alumina-silicate precursors (carbon ash and processed metallurgical slag) with cheaper and less commonly utilized wastes. Thus, clay brick waste, residual building concrete, and flat glass waste resulted from building demolition were introduced in manufacturing mixture after reducing the carbon ash and slag content. Many previous works in the literature have confirmed that carbon ash and metallurgical slag are the most suitable industrial secondary products usable in the preparing process of geopolymer composites, but their intense demand has contributed to the trend of increasing their price. Numerous alternative materials with cementitious and pozzolanic properties available in the world offer the possibility of using them for similar purposes. Even if applying these wastes does not result in reaching the qualitative level of carbon ash/slag-based geopolymer, their appropriate combination is beneficial and the current work used different experimental versions including clay brick, residual concrete, and flat glass resulted from building demolition, associated with significantly reduced consumption of ash and slag.
Keywords: geopolymer composite; waste; alumina-silicate; clay brick; building concrete; flat glass